Discovery and modelling of a flattening of the positive cyclotron line/luminosity relation in GX 304−1 with RXTE. Issue 3 (12th December 2016) - Rothschild, Richard E.; Kühnel, Matthias; Pottschmidt, Katja; Hemphill, Paul; Postnov, Konstantin; Gornostaev, Mikhail; Shakura, Nikolai; Fürst, Felix; Wilms, Jörn; Staubert, Rüdiger; Klochkov, Dmitry
Abstract: The Rossi X-ray Timing Explorer ( RXTE ) observed four outbursts of the accreting X-ray binary transient source, GX 304−1 in 2010 and 2011. We present results of detailed 3–100 keV spectral analysis of 69 separate observations, and report a positive correlation between cyclotron line parameters, as well as other spectral parameters, with power-law flux. The cyclotron line energy, width and depth versus flux, and thus luminosity, correlations show a flattening of the relationships with increasing luminosity, which are well described by quasi-spherical or disc accretion that yield the surface magnetic field to be ∼5 × 10 12 Gauss. Since HEXTE (High Energy X-ray Timing Experiment) cluster A was fixed aligned with the Proportional Counter Array field of view and cluster B was fixed viewing a background region 1 _.^° 5 off of the source direction during these observations near the end of the RXTE mission, the cluster A background was estimated from cluster B events using HEXTEBACKEST . This made possible the detection of the ∼55 keV cyclotron line and an accurate measurement of the continuum. Correlations of all spectral parameters with the primary 2–10 keV power-law flux reveal it to be the primary driver of the spectral shape. The accretion is found to be in the collisionless shock braking regime.